2016
DOI: 10.1038/srep28257
|View full text |Cite
|
Sign up to set email alerts
|

Multi-targeted metagenetic analysis of the influence of climate and environmental parameters on soil microbial communities along an elevational gradient

Abstract: Mountain elevation gradients are invaluable sites for understanding the effects of climate change on ecosystem function, community structure and distribution. However, relatively little is known about the impact on soil microbial communities, in spite of their importance for the functioning of the soil ecosystem. Previous studies of microbial diversity along elevational gradients were often limited by confounding variables such as vegetation, pH, and nutrients. Here, we utilised a transect in the Pyrenees esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 57 publications
3
48
1
1
Order By: Relevance
“…In contrast, with a few exceptions (Bahram et al 2018), most studies find no increase in soil microbial diversity from polar to equatorial regions (Fenchel and Finlay 2004, Fuhrman 2009, Fierer et al 2011, Hendershot et al 2017. As a consequence, studies aiming to examine the relationship between plant diversity and soil microbial diversity across biogeographic scales find weak (Bryant et al 2008, Prober et al 2015, or even no correlations (Lanz en et al 2016, Cameron et al 2019. As a consequence, studies aiming to examine the relationship between plant diversity and soil microbial diversity across biogeographic scales find weak (Bryant et al 2008, Prober et al 2015, or even no correlations (Lanz en et al 2016, Cameron et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, with a few exceptions (Bahram et al 2018), most studies find no increase in soil microbial diversity from polar to equatorial regions (Fenchel and Finlay 2004, Fuhrman 2009, Fierer et al 2011, Hendershot et al 2017. As a consequence, studies aiming to examine the relationship between plant diversity and soil microbial diversity across biogeographic scales find weak (Bryant et al 2008, Prober et al 2015, or even no correlations (Lanz en et al 2016, Cameron et al 2019. As a consequence, studies aiming to examine the relationship between plant diversity and soil microbial diversity across biogeographic scales find weak (Bryant et al 2008, Prober et al 2015, or even no correlations (Lanz en et al 2016, Cameron et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, soil microbial diversity patterns vary widely along elevation gradients, where monotonic declines (Bryant et al 2008), unimodal patterns (Liu et al 2016a), and no relationships (Fierer et al 2011, Shen et al 2014 with increasing elevation have all been reported. As a consequence, studies aiming to examine the relationship between plant diversity and soil microbial diversity across biogeographic scales find weak (Bryant et al 2008, Prober et al 2015, or even no correlations (Lanz en et al 2016, Cameron et al 2019. These conflicting results suggest that the relationship between soil microbial diversity and plant diversity might differ across biomes and spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these observations, in our second iteration of this practical the THW cohort performed 16S rRNA gene amplification with primers targeting the V4 region. This approach resulted in similar soil-community profiles to other soil-microbiome studies (Lanzén et al, 2016;Thompson et al, 2017;Tian et al, 2017).…”
mentioning
confidence: 63%
“…Based on these observations, in our second iteration of this practical the THW cohort performed 16S rRNA gene amplification with primers targeted to the V4 region and used the higher fidelity Q5 polymerase. This approach resulted in similar soil-community profiles to other soil-microbiome studies (Lanzén et al, 2016;Thompson et al, 2017;Tian et al, 2017). We maintained sterility in these negative controls by returning soil samples to the laboratory and assembling the iChips in laminar flow cabinets before returning the samples to the field for initial growth.…”
Section: Protocol Pitfalls and Improvementsmentioning
confidence: 96%
“…Several distinct patterns have been also described for archaeal (Singh et al, 2014;Wang et al, 2015a;Siles and Margesin, 2016;Bardelli et al, 2017) and fungal communities (Meng et al, 2013;Wang et al, 2015b;Siles and Margesin, 2016). The processes driving this variation in microbial communities have been mainly related to abiotic factors (Lanz en et al, 2016;Siles and Margesin, 2016), and the role of biotic interactions such as competition has long been neglected. However, there is no good reason to reject a role for biotic processes in driving elevational patterns exhibited by microbial communities (Goberna et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%